Physical Literacy Profile of Indonesian Children Aged 6-8 Years: Preliminary Normative Data and Interpretive Guidelines Using the Physical Literacy in Children Questionnaire (PL-C Quest) - Didin Budiman; Agus Mahendra; Achmad Syakur Fahri; Messa Rahmi; Ricky Wibowo; Mukhlisin Mukhlisin; Dian Budiana; Suherman Slamet; Anira Anira (Universitas Negeri Semarang, 2026)
Background: Physical literacy (PL) is recognized as a fundamental concept for encouraging children to engage in lifelong physical activity and achieve healthy outcomes. However, in Indonesia, normative data and interpretive criteria for assessing children’s physical literacy are lacking. The Physical Literacy in Children Questionnaire (PL-C Quest) is a validated pictorial self-report tool, but no interpretation guidelines exist for its use in Indonesian contexts. Objectives: This study aimed to establish baseline normative data and preliminary interpretive guidelines for the PL-C Quest in Indonesian children aged 6–8 years. Method: A cross-sectional descriptive study was conducted with 50 children (19 boys, 31 girls) aged 6–8 years, recruited from Indonesian elementary schools. Each child completed the 30-item PL-C Quest, which uses cartoon illustrations to assess perceived physical literacy across four domains (Physical, Psychological, Social, Cognitive). Descriptive statistics (means, standard deviations, ranges, percentiles) were calculated for total and domain scores. Preliminary percentile-based categories were developed to interpret individual scores. Result: The mean overall PL-C Quest score was 90.22 ± 11.74 (out of 120; 75.2% of the maximum), with a median of 92 and range of 59–112. Domain scores (as percentages of their maximums) were highest in the social domain (79.3%), followed by Physical (77.0%), Psychological (72.4%), and Cognitive (71.6%). Five interpretive categories were defined: Very High, ≥102 points, High, 97–102, Moderate, 80–97, Low, 71–80, and Very Low, ≤71. Boys scored marginally higher on average than girls (91.53 vs. 89.42), and scores showed a slight decline with increasing age (mean for 6-year-olds 98.67; 7-year-olds 90.84; 8-year-olds 87.20). Conclusion: This study provides the first normative data on physical literacy for Indonesian children, revealing generally high perceived physical literacy with strengths in social interaction and physical competence. Areas for improvement include the cognitive and psychological domains. The new percentile-based categories offer educators and practitioners practical benchmarks for interpreting PL-C Quest scores and identifying children who may benefit from targeted interventions. These findings supply a crucial baseline for developing physical literacy programs and future research in Indonesia.